The everlasting empire : the political culture of ancient China and its imperial legacy - Pines, Yuri (Princeton University Press, 2012)
"Established in 221 BCE, the Chinese empire lasted for 2,132 years before being replaced by the Republic of China in 1912. During its two millennia, the empire endured internal wars, foreign incursions, alien occupations, and devastating rebellions--yet fundamental institutional, sociopolitical, and cultural features of the empire remained intact. The Everlasting Empire traces the roots of the Chinese empire's exceptional longevity and unparalleled political durability, and shows how lessons from the imperial past are relevant for China today.